Technology, society and e-government: in search of an eclectic framework. (8th June 2007) - As-Saber, Sharif; Hossain, Khalid; Srivastava, Aashish
E-government is often considered as a dynamic mechanism to establish citizen-centric, more transparent and more accountable government system. However, such mechanism is often thwarted by a host of intricacies contributed by the lack of ICT resources and infrastructure, unequal access to technology, low e-literacy rate and the lack of appropriate government policy initiatives and commitments. The dilemma surrounding the concept of privacy versus openness and the connectivity between the wider society and technology may also impact on the e-government implementation process and its success. This paper initially discusses the challenges to successful implementation of e-government. Subsequently, from a developing country perspective, an eclectic theoretical framework is proposed. The framework aims at identifying the dynamic relationship pattern between the government and the various stakeholders including citizens, and addresses how the various environmental factors, such as politics, bureaucracy, technology and culture, may contribute to the e-government success.